Pengaruh Kualitas Website E-Commerce, Kepercayaan, Persepsi Risiko dan Norma Subyektif terhadap Minat Beli Secara Online di bukalapak.com - Ady Achadi; Mayla Surveyandini; Agus Prabawa (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This study aims to analyze the effect of e-commerce website quality, trust, risk perception, and subjective norms on buying interest at Bukalapak.com. This type of research is quantitative. The sampling technique used was purposive sampling. The research method uses Structural Equation Modeling (SEM). The results showed that the quality of the e-commerce website, trust and risk perception have a significant positive effect on buying interest at Bukalapak.com. Subjective norms have not significant effect on online buying interest at Bukalapak.com. This finding implies the policy of the need to create and manage a practical website with a good appearance, using language that is easy to understand and the website is easily accessible to consumers. In addition, it provides product safety guarantees and guarantees against the risk of damage and loss of products purchased by consumers.